Focus group: The incoherent aperture - Callejo, Javier (Sociolinguistic Studies, 2002)
As every social practice, the quotidian discourse is built by coherence and incoherences. In Bourdieu words, that is the logic of the practices Because is partially incoherent, the coherence is a work to the talker and to the audience. From social order perspective and as Freud pointed on, the coherence is a work from the censorship that depens on the inmediate context of discourse, from the social situation. In spite of this, conversational methods of social research as the interview, what are in very formal inmediat contexts, produce only the coherent dimension of discourse. The discussion group is a conversational method that gather the incoherent dimension. This conception follows Jesús Ibáñez, Ángel de Lucas, Alfonso Ortí and Luis Enrique Alonso works. So, the discussion group is a method nearer of casual or spontaneous discourse, where the social conflicts plays. This conception is a source of big capacity for this method and a border, because everything no is talked in public situations.